The influence of work environment and work motivation on employee performance at PT XXX - Dini Sugiarti; Uce Karna Suganda (Journal Research of Social Science, Economics, and Management, 2025)
In the increasingly competitive banking industry, employee performance has become a critical factor in determining organizational success. This study aims to analyze the influence of work environment and work motivation on the performance of marketing division employees at PT XXX. The pre-survey results indicated that the work environment was perceived as suboptimal, particularly in terms of facilities, workplace comfort, and collaborative support. Work motivation was largely driven by rewards, recognition, and achievement orientation, although weaknesses remained in the clarity of performance targets and promotion opportunities. A quantitative approach was employed using survey methods with 35 respondents and multiple linear regression analysis was applied to test the hypotheses. The findings reveal that the work environment has a significant effect on employee performance with a regression coefficient of 0.956, while work motivation also exerts a significant effect with a regression coefficient of 0.474. Simultaneously, both variables significantly influence employee performance, contributing 54.6% to performance variation, with the remaining 45.4% explained by other factors outside the model. These results highlight that improving the quality of the work environment and enhancing employee motivation are strategic steps to strengthen the performance of PT XXX’s marketing division employees.